The Elental(®) elemental diet for chemoradiotherapy-induced oral mucositis: A prospective study in patients with oral squamous cell carcinoma - Harada, Koji (Mol Clin Oncol, 2019)
Oral mucositis is a common adverse effect of cancer treatment that can increase the risk for local and systemic infection. This prospective study was designed to evaluate the preventive effects of an amino-acid-rich elemental diet (ED), Elental(®), on radiotherapy- or chemoradiotherapy-induced mucositis in oral squamous cell carcinoma (OSCC) patients. Fifty patients were enrolled in this prospective study, who had received radiation (60–70 Gy) with/without chemotherapy [S-1, UFT, cisplatin (CDDP), docetaxel (DOC) plus CDDP, or Cetuximab]. The Elental(®) group (25 patients) had received Elental(®) during treatment, and the control group (25 patients) had not. Multivariate logistic regression analysis was used to identify the factors related to abatement of oral mucositis. A comparison of the rates of completion of chemoradiation treatments as well as the nutritional or inflammatory status between Elental(®) and control groups was performed. Multivariate analysis indicated that most of the patients who received Elental(®) suffered from a lower degree of mucositis and showed significantly improved rate of completion of chemoradiation (no interruption) compared to the control group. There was a significant difference between the Elental(®) group and the control group in terms of the mean change of C-reactive protein (CRP) levels in blood serum; however, there was no significant difference in terms of a mean change of body weight and total protein level in blood serum before and after chemoradiation. Our study shows that the Elental(®) elemental diet could be useful for the treatment of oral mucositis induced by chemoradiation. Elental(®) might also promote improved completion rates of chemoradiotherapy in OSCC patients.